Does childbirth change the gender gap in well-being between partners? - Veronika Plachá (Charles University in Prague, Institute of Economic Studies (IES), 2024)
This study examines gender disparities beyond pay gaps, focusing on the impact of childbirth on overall well-being. Traditional gender roles, especially in parenting, lead to unequal divisions of labor and affect both partners' well-being, yet the shift in well-being after childbirth remains underexplored. Utilizing data from the 2013 and 2018 EU SILC surveys, the study investigates the well-being gap between mothers and fathers, revealing that childbirth significantly influences parents' subjective well-being. Mothers tend to experience a longer-lasting positive effect, peaking during the newborn stage and gradually diminishing as children grow older, while fathers' wellbeing boost is shorter-lived, typically fading after the child's first year. The findings also indicate that the well-being gap between mothers and fathers has widened over time, especially during the preschool years, underscoring the complex dynamics of well-being among parents.
Keywords: J13; J16; I31; J12; 330; Subjective well-being; Gender disparities; Childbirth; Well-being gap